Vitamin D supplementation does not prevent the testosterone decline in males with advanced heart failure: the EVITA trial. - Zittermann, Armin; Ernst, Jana B.; Prokop, Sylvana; Fuchs, Uwe; Dreier, Jens; Kuhn, Joachim; Knabbe, Cornelius; Berthold, Heiner K.; Gouni-Berthold, Ioanna; Gummert, Jan F.; Börgermann, Jochen; Pilz, Stefan (European Journal of Nutrition, 2019)
Purpose: Observational studies indicate a positive association between circulating 25-hydroxyvitamin D (25OHD) and testosterone (T) concentrations. Because low 25OHD concentrations and T deficiency are considered to be a generalized phenomenon in patients with advanced heart failure (HF), we aimed to investigate whether vitamin D supplementation has beneficial effects on T indices in these patients. Methods: In a pre-specified secondary analysis of the EVITA (effect of vitamin D on mortality in heart failure) randomized controlled trial, we analyzed in male subjects with 25OHD concentrations < 75 nmol/L the effect of a daily vitamin D3 supplement of 4000 IU for 3 years (n = 71) vs. placebo (n = 62) on total T (TT), sex hormone-binding globulin (SHBG), free T (fT), and bioactive T (BAT). We assessed changes from baseline until study termination and between-group differences at study termination. Results: 25OHD increased in the placebo group from 36.6 nmol/L by 9.2 nmol/L (95% CI 3.2–15.1 nmol/L; P = 0.003) and in the vitamin D group from 36.5 nmol/L by 63.9 nmol/L (95% CI 52.6–75.3 nmol/L; P < 0.001), with a significant between-group difference at study termination (P < 0.001). TT and SHBG concentrations did not change significantly, neither in the placebo group nor in the vitamin D group (P = 0.845–0.082), but concentrations of fT and BAT declined significantly in both groups (P = 0.025–0.008). At study termination, there were no between-group differences in TT (P = 0.612), SHBG (P = 0.393), fT (P = 0.861), or BAT (P = 0.960). Conclusions: In male patients with advanced HF and low 25OHD concentrations, a daily vitamin D3 supplement of 4000 IU for 3 years did not prevent the decline in testosterone indices.